2014
DOI: 10.2152/jmi.61.156
|View full text |Cite
|
Sign up to set email alerts
|

Community-based clinical education increases motivation of medical students to medicine of remote area -comparison between lecture and practice-

Abstract: In this study, we administered a questionnaire to medical students to evaluate the effect of community-based clinical education on their attitudes to community medicine and medicine in remote area. Questionnaires were given 4 times to all the students from first-year to sixth-year. Of 95 students, 65 students (68.4%) who completed all questionnaires, were used in this study. The intensity of students' attitudes was estimated by using visual analogue scale. The intensity of interest, a sense of fulfillment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…These items were chosen because they were listed as factors related to working area decisions by the WHO [22]. The attitudes toward RH were described as "I want to work in a rural area" ("rural") [15]. These attitudes (i.e., "worthwhile," "confidence," and "rural") were obtained using a visual analogue scale (VAS; 0 -100 mm) and were treated as continuous variables.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These items were chosen because they were listed as factors related to working area decisions by the WHO [22]. The attitudes toward RH were described as "I want to work in a rural area" ("rural") [15]. These attitudes (i.e., "worthwhile," "confidence," and "rural") were obtained using a visual analogue scale (VAS; 0 -100 mm) and were treated as continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire (available in Additional File 1 ) was developed through literature review and discussion between the co-researchers to improve its validity [ 21 ]. The questionnaire used in the previous study evaluating the short-term effects of the CBCT [ 14 , 15 ] was adapted for the questionnaire of this study concerning the CBCT programs and the perceptions for CH and RH. Furthermore, reviewing the previous study, we defined the CH, the CBCT, and the rural areas described above to improve its validity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that most medical students are interested in family medicine, 6 ) and that some do intend to work in rural areas 7 ) following their community-based clerkships.…”
Section: Introductionmentioning
confidence: 99%
“…It was useful to inform the charm and importance in working at medical facilities in remote area to medical students, but simultaneously may inform a variety of problems of medicine in remote area such as a shortage of doctors to them (9 -12). Our previous report showed that the community -based practice is more meaningful in increasing the motivation in working in remote area medicine than the lecture, and suggesting that it is important to prepare more courses to experience community medicine to increase the number of physicians who desire to work in remote area (13).…”
Section: Introductionmentioning
confidence: 99%